An Analysis of Reading Material in the English Textbook "My Next Words" Based on Merdeka Belajar Curriculum for the Fourth Grade of Elementary School - Ana Haqiqotul Millah; Haryanto Haryanto (Journal on Education, 2024)
This study aims to describe whether the reading material in the English textbook "My Next Words" for Grade 4 Elementary School meets the criteria of the Free Learning Curriculum and the BSNP framework for textbook evaluation. This research is expected to provide insights to understand the quality of reading material. This research is designed as a content analysis in the form of qualitative descriptive research, with the results described in a narrative form. The checklist was developed based on the BSNP (2014) framework for textbook evaluation, focusing on the area of relevance of the reading material to the Merdeka Belajar curriculum and the content aspects, aspects of language usage, readability, and presentation aspects. Data was collected from the reading section of the English textbook. The English textbook "My Next Words" is published by the National Ministry of Education. The findings of this study show that the reading material in the English textbook "My Next Words" is relevant to the Merdeka Belajar Curriculum and the BSNP framework for textbook evaluation—results of the analysis of curriculum criteria relevance. According to the results of the reading material analysis, each aspect based on the content of the adopted textbook from the BSNP meets both the category, the content aspect, the usage and readability aspect of the language, and the presentation aspect. As a result, the 2017 revised edition of the K13-based English textbook can be used in the Free Learning curriculum. However, some things are still lacking in learning outcomes in the self-learning curriculum. So that teachers can adapt to the situation by making innovations in teaching-learning activities.